Kappa: Makhluk Mitologis Penjaga Sungai dalam Cerita Rakyat Jepang - Ida Ayu Laksmita Sari (JENTERA: Jurnal Kajian Sastra, 2020)
This article discusses one of the Japanese mythological creatures in the youkai category, the kappa which is believed to be river guardians. Data is taken from the anthology of Japanese folklore Mangga Nippon Mukashi Banashi 101 edited by Sayumi Kawauchi. Folklore used as the object of research are two titles that were chosen selectively which are "Kasa Uri Ohana" (Ohana the Umbrella Seller) and "Kappa no Amagoi " (Rain Calling Prayer from Kappa). Data were analyzed with Peirce's semiotic trichotomy theory, namely icons, indices and symbols, and literary anthropological theory. This article concluded three things related to the form of a kappa, where they are believed to be present and the status of kappa in the Japanese belief system. Kappa in Japanese mythology resembles a frog's shape but has scales and has a weakness in its skull. Kappa is believed to live in rivers in Japan. Kappa is present and has a special place in Japanese society's trust, evidenced by the existence of kappa temples. Unlike other Japanese youkai, the kappa is believed that before the form of the kappa he was a god whose rank was demoted, therefore it was believed that he could be begged for rain. The existence of kappa, thus, not only has negative attributes but also positive ones. AbstrakArtikel ini mengkaji sosok kappa, salah satu makhluk mitologis dan gaib Jepang yang masuk kategori youkai (hantu) dan dipercaya sebagai makhluk penjaga sungai. Data diambil dari antologi cerita rakyat Jepang Mangga Nippon Mukashi Banashi 101 dengan editor Sayumi Kawauchi. Cerita rakyat yang digunakan sebagai objek penelitian ada dua judul yang dipilih secara selektif, yaitu “Kasa Uri Ohana” (Ohana si Penjual Payung) dan “Kappa no Amagoi” (‘Doa Pemanggil Hujan dari Kappa). Data dianalisis dengan teori trikotomi semiotika Peirce, yaitu ikon, indeks, dan simbol, serta teori antropologi sastra. Artikel ini menyimpulkan tiga hal, yaitu wujud kappa, tempat mereka dipercaya hadir, dan eksistensi kappa dalam sistem kepercayaan Jepang. Kappa dalam mitologi Jepang menyerupai wujud katak, tetapi bersisik dan memiliki kelemahan di tempurung kepalanya. Makhluk gaib ini dipercaya tinggal dan sekaligus menjadi penjaga sungai-sungai di Jepang. Kappa hadir dan memiliki tempat yang khusus dalam kepercayaan masyarakat Jepang, yang dibuktikan dengan terdapatnya kuil kappa. Tidak seperti youkai Jepang lainnya, kappa dipercaya bahwa sebelum berwujud kappa dia adalah dewa yang derajatnya diturunkan. Oleh karena itu, kappa diyakini bisa dimohon untuk mendatangkan hujan. Dengan demikian, eksistensi kappa tidak saja memiliki atribut negatif, tetapi juga positif.